Rancang Bangun Aplikasi Aplikasi Iuran Sampah RT/RW Menggunakan Metode Rapid Application Development Berbasis Android - Aditya Pratomo Sutrisno; Ariq Cahya Wardhana; Auliya Burhanuddin (STMIK Budi Darma, 2022)
RT047/RW008 or Jl. Aries is a Neighborhood Association located in Sungai Besar Village, Banjarbaru City, South Kalimantan province. Within this RT environment, weekly and monthly activities are often held. One of the activities in this area is the monthly waste fee. This activity has been around for a long time when this environment was formed. However, in this monthly waste fee activity, we still use the recording method by recording data on a physical citizen membership fee card. In addition, the manufacture of this garbage contribution card still uses the service of making a contribution card which requires traveling and also incurs some costs. In the process of monthly waste contribution activities, it often results in the loss or damage of the citizen membership dues card, in which the treasurer has to make another card at the contribution card making service. Based on the problems found, a solution to the problem that can be found is to design an Android-based application that can run on Android Smartphone devices. This application will be designed using the Rapid Application Development method which will go through the process of data collection to application design. This application can perform the administrative process of digital waste dues. In addition, in the application there is also a reminder feature that will be sent to Whatsapp for every registered member of the group. Because this application runs on Android Smartphone devices, it can make it easier for users to input data and change data anywhere and anytime. The method used for designing this application is to analyze to find out what is needed in an application that you want to build. The final result of the implementation process in the form of Java programming and test results by users. By using the white box testing and black box testing methods, the result is that the application can run well and in accordance with the needs required by the user. With this android application, the RT environment can be more focused and become an RT that can be in line with current technological developments